Downregulation of vascular endothelial-cadherin expression is associated with an increase in vascular tumor growth and hemorrhagic complications - Zanetta, Lucia; Corada, Monica; Lampugnani, Maria Grazia; Zanetti, Adriana; Breviario, Ferruccio; Moons, Lieve; Carmeliet, Peter; Pepper, Michael S.; Dejana, Elisabetta (Thrombosis and Haemostasis, 2005)
The pathogenesis of vascular tumors such as angiosarcomas is poorly understood. Cadherin expression inversely correlates with tumor malignancy and the endothelial specific VE-cadherin is low or absent in angiosarcomas, suggesting an inhibitory role for this protein in tumor progression. In this paper we report that Pmy T VE-cadherin null (VEC null) endothelial cells form larger vascular tumors in nude mice when injected subcutaneously as compared to isogenic VE-cadherin positive (VEC pos) cells. This effect requires the association of β-catenin to VE-cadherin, since a VE-cadherin mutant lacking the domain responsible for β-catenin binding (Δβcat) cannot rescue the phenotype. In VEC null cells β-catenin is phosphorylated and partly degraded. N-cadherin is increased and detected at junctions. VEC null cells also present an altered fibrinolytic activity with increases in tPA, uPA, uPAR and a strong reduction in PAI-1, which may be correlated to the high incidence of abrupt hemorrhages in VEC null tumors. Overall, these data strongly suggest that downregulation of VE-cadherin in endothelial tumors may have important consequences for tumor growth and bleeding complications.
Keywords: VE-cadherin; fibrinolysis; PAI-1; vascular tumors